Idiopathic Interstitial Pneumonias and COVID-19 Pneumonia: Review of the Main Radiological Features and Differential Diagnosis - Alessia Guarnera; Elena Santini; Pierfrancesco Podda (Tomography, 2021)
COVID-19 pneumonia represents a challenging health emergency, due to the disproportion between the high transmissibility, morbidity, and mortality of the virus and healthcare systems possibilities. Literature has mainly focused on COVID-19 pneumonia clinical-radiological diagnosis and therapy, and on the most common differential diagnoses, while few papers investigated rare COVID-19 pneumonia differential diagnoses or the overlapping of COVID-19 pneumonia on pre-existing lung pathologies. This article presents the main radiological characteristics of COVID-19 pneumonia and Idiopathic Interstitial Pneumonias (IIPs) to identify key radiological features for a differential diagnosis among IIPs, and between IIPs and COVID-19 pneumonia. COVID-19 pneumonia differential diagnosis with IIPs is challenging, since these entities may share common radiological findings as ground glass opacities, crazy paving patterns, and consolidations. Multidisciplinary discussion is crucial to reach a final and correct diagnosis. Radiologists have a pivotal role in identifying COVID-19 pneumonia patterns, reporting possible overlapping with long-lasting lung diseases, and suggesting potential differential diagnoses. An optimal evaluation of HRTC may help in containing the disease, in promoting better treatment for patients, and in providing an efficient allocation of human and economic resources.